The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1037/edu0000519
|View full text |Cite
|
Sign up to set email alerts
|

Class-average achievement and individual achievement development: Testing achievement composition and peer spillover effects using five German longitudinal studies.

Abstract: In recent studies, the existence and relevance of achievement composition effects on students' individual achievement have been called into question because of the methodological challenges arising in multilevel analyses. Our study examined how class-average achievement is related to students' achievement development across one school year. We used data from Germany, which has a secondary school system with large achievement differences between schools and classrooms due to rigid, explicit betweenschool tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 99 publications
(221 reference statements)
1
6
0
Order By: Relevance
“…Thus, students whose classmates had, on average, higher language proficiency concerning general academic vocabulary and comprehension of connectives at the beginning of the school year showed larger learning gains over time. On the one hand, this finding adds to a large body of research that provided evidence for compositional effects for different age groups and domains, including language proficiency (e.g., Becker et al, 2022;Foster et al, 2020;Hanushek et al, 2003;Schmerse, 2021). On the other hand, it extends prior research on inquiry-based science instruction, which typically did not adhere to compositional effects.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, students whose classmates had, on average, higher language proficiency concerning general academic vocabulary and comprehension of connectives at the beginning of the school year showed larger learning gains over time. On the one hand, this finding adds to a large body of research that provided evidence for compositional effects for different age groups and domains, including language proficiency (e.g., Becker et al, 2022;Foster et al, 2020;Hanushek et al, 2003;Schmerse, 2021). On the other hand, it extends prior research on inquiry-based science instruction, which typically did not adhere to compositional effects.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, student achievement is related to characteristics of the classroom composition. Thus, students typically show larger learning gains when they are grouped with high-achieving students (Becker et al, 2022;Schmerse, 2021) or with students from families with high socioeconomic status (SES; Rjosk et al, 2014;van Ewijk & Sleegers, 2010). Classroom characteristics are, in turn, associated with instructional processes (Fauth et al, 2021;Kuger et al, 2016;Rjosk et al, 2014).…”
Section: The Present Studymentioning
confidence: 99%
“…The distribution of individual beliefs at the aggregate level is conceptualized as an indicator of the institutional diversity culture. These contextual effects, also termed composition effects, are currently the subject of intense discussion (Becker et al, 2021; Harker & Tymms, 2004). In the following, we outline findings from each of the three approaches to the study of institutional acculturation norms.…”
Section: Acculturation Beliefs As Individual Resources and Developmen...mentioning
confidence: 99%
“…As outlined above, the latter finding might constitute a ceiling effect: Students in schools with a higher than average ICT performance in Grade 9 seem to improve less than students in schools with a lower than average prior ICT performance. Findings on effects of the class or school-related achievement composition on the development of students' achievement have been mixed, with some studies suggesting positive effects (Becker et al, 2022;Stäbler et al, 2017) but others suggesting zero or negative effects (Dicke et al, 2018;Televantou et al, 2021). Notably, most of these studies have considered math or language achievement, and we are not aware of any studies that have considered ICT literacy in this context.…”
Section: Discussionmentioning
confidence: 97%
“…In one of these studies, Göllner et al (2018) found that the average level of socioeconomic background at a school was positively associated with educational attainment and expectations as well as income and occupational prestige 11 years later. Furthermore, Becker et al (2022) found support for the positive effects of achievementrelated peer composition, over and above tracking effects, suggesting that students' learning progress might benefit from being surrounded by peers with a higher average level of performance. Other prior studies on this topic have found zero or even negative associations between school composition and student achievement (Dicke et al, 2018).…”
Section: Contextual School Effectsmentioning
confidence: 95%